Ethnobotanical and Plant Profile Studies at Karimunjawa Village of Jepara Regency, Central Java - Nurhidayati, Tutik; Saptarini, Dian; Jadid, Nurul (IPTEK The Journal for Technology and Science, 2009)
Ethnobotanical and plant profile studies that had been conducted at Karimunajawa Village of Jepara Regency were aimed to elucidate plants used by the Karimunjawa villagers and typical plants of the Karimunjawa as well as their usage. The method used for this study was questionnaire, structured and semi-structured interviews. Conditions of Karimunjawa typi-cal plants in their natural habitats were measured through bell transects that were determined based on questionnaire previously filled by the villagers. Results of the study showed that there were 39 species of wild and cultivated plants used by villagers. The plants were used for building materials (39.77%), food (23.86%), handi-craft and souvenir (23.29%), furniture (5.11%), ship construction (3.40%), medicine (2.84%), and fuel wood (1.70%). There were three species of typical plants found in the Karimunjawa Islands, i.e. Dewadaru (Fragraea elliptica), Setigi (Pemphis acidula), and Kalimasada (Cordia subcordata). Profile of the typical plants indica-ted that at the Karimunjawa Village there were sixty four individual Dewadaru and two Setigi in their narural habitats. However, no Kalimasada was found in its origi-nal habitat; the Kalimasada found in this area was that of previously planted.